Reformulasi Kerangka Sharia Sustainability Accounting: Studi Normatif pada Industri Halal - Moh Eko Saputro; Siti Fatimah; Ardhana Reswari Hasna Pratista (LP2M Politeknik Jambi, 2025)
This study aims to reformulate a conceptual framework for sustainability accounting based on Islamic values, specifically tailored for the halal industry. While global sustainability reporting standards such as the Global Reporting Initiative (GRI) and IFRS Sustainability Disclosure Standards have become widely adopted, they remain secular and value-neutral, often lacking spiritual and ethical dimensions essential in Islamic business ethics. Through a normative-conceptual approach, this research critically examines the normative gaps in conventional sustainability frameworks when applied to halal enterprises and proposes an alternative model rooted in maqashid al-shariah and Islamic ethics (akhlaq). The scope of the study includes a comprehensive literature analysis of conventional standards, classical Islamic legal texts, and contemporary fatwas and regulations relevant to halal enterprises in Indonesia. The findings highlight three key gaps: the absence of spiritual accountability, the lack of faith-based social justice indicators (e.g., zakat, waqf), and the need for ethical environmental stewardship based on the concept of khalifah and amanah. As a result, the study proposes a new sustainability accounting framework consisting of three integrated dimensions spiritual, social, and ecological—each aligned with specific Islamic values and reporting indicators. This framework emphasizes dual accountability: to society and to God. The conclusion affirms that sustainability accounting in the halal industry must evolve beyond profit and compliance, toward a spiritually grounded, ethically driven model that reflects the holistic nature of Islamic business